1982
DOI: 10.1007/bf02670058
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur compounds affecting processing of rapeseed

Abstract: A characteristic feature of cruciferous oilseeds is a high level of sulfur compounds as sulfur‐containing amino acids and glucosinolates which determine the nutritional value of rapeseed meal and affect processing factors in oil mills. During rapeseed processing, products of glucosinolate splitting are liberated and attack metal and, as a result, a specific sulfur corrosion of oil mill equipment develops. The most exposed are cooker, toaster and transporters of wet meal. The results of industrial investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…In fact, sulphur in oils could be present in a number of forms which may have different effects on the flavour of the final oil. Rutkowski, Gwizad, and Krygier (1982) confirmed that sulphur compounds in rapeseed oil occur in volatile, thermo labile and nonvolatile forms. Their relative proportions vary on the particular stage of the refining process.…”
Section: Sulphur Compoundsmentioning
confidence: 54%
See 1 more Smart Citation
“…In fact, sulphur in oils could be present in a number of forms which may have different effects on the flavour of the final oil. Rutkowski, Gwizad, and Krygier (1982) confirmed that sulphur compounds in rapeseed oil occur in volatile, thermo labile and nonvolatile forms. Their relative proportions vary on the particular stage of the refining process.…”
Section: Sulphur Compoundsmentioning
confidence: 54%
“…Their relative proportions vary on the particular stage of the refining process. Even present in trace quantities, the sulphur compounds attract the attention of scientists because they inhibit oil hardening processes and impact characteristics odours to the oils (Rutkowski et al, 1982). We suppose that the sensitivity of the used HS-SPME GC-MS was not high enough for the detection of further sulphur compounds.…”
Section: Sulphur Compoundsmentioning
confidence: 99%
“…The same is true for the conditioning of rapeseeds prior to oil extraction the aim of which is, among others, to inactive native enzymes including myrosinase [29, 411. During that process flaked rapeseeds are gradually heated for a long time (70-105 "C, 45 min) [28] which favours glucosinolates breakdown due to their contact with myrosinase as a result of destruction of the seeds cell structure. Improperly applied hydrothermal treatment may occasionally, instead of deactivating, inactivate myrosinase thus favouring glucosinolate degradation with all its negative consequences [5,13,14,28,47,59]. The necessity for myrosinase inactivation in the rapeseeds prepared for oil extraction does not seem to evoke any doubts; it is the method itself applied in industry that is in question.…”
Section: Traditional Technology and Its Modificationsmentioning
confidence: 99%
“…They suggested that volatile sulfur compounds are suspected of catalyst poisoning. Most of the sulfur compounds are believed to originate from decomposition of glucosinolates (Rutkowski et al 1982). They are mainly isothiocynates, thiocynates, and sulfates, which also can further decompose to give oxazolidine-2-thione, hydrogen sulfide, and several other sulfur compounds as secondary decomposition products.…”
Section: Canola Oil and Its Characteristicsmentioning
confidence: 99%